Visitors’ satisfaction towards wildlife observation tower in Taman Negara, Kuala Tahan, Pahang - Muda, Nor Ilyana (2019)
The wildlife observation tower, a structure built to observe wildlife, was first built in the early 1960s in Taman Negara, Kuala Tahan, Pahang. There are six towers that were built, but only four can be used. This paper discussed the level of visitors’ satisfaction and determined the factors that influence the level of satisfaction of the wildlife observation towers. Data captured from visitors was used to achieve the objective of this study by conducting a questionnaire survey at Taman Negara, Kuala Tahan, Pahang from 15 January to 31 March 2019. Visitor satisfaction levels towards the wildlife observation tower were measured using the five-point Likert Scale. Results of the questionnaire survey of 100 respondents shows that visitors were satisfied with the overall facilities provided with an overall satisfaction index of 3.63 of 4.00. The highest mean score was 4.38 obtained for “Recommendation of the activity to others”. The lowest mean score was 2.94 obtained for “Provide bins to visitors ease”. Multiple regression analysis results show six factors significantly influencing overall visitors satisfaction which are, visitor satisfaction on cleanliness carries the strongest predictors, followed by good hospitality services by local community, easy accessibility, provided bins to each tower, sufficient of the facilities provided and information board provided. Park management needs to maintain the standard of facilities provided to ensure that the product offered guarantees the satisfaction of visitors and is able to obtain the ideal tourist experience for visitors by focusing on the travel motives and the quality of service delivered at the park.